Navigating materials adaptation: English teachers’ experiences in Turkish secondary schools - Müzeyyen Nazlı Güngör; David Read; Mustafa Akın Güngör (Literacy Trek)
Teachers often adapt materials to create more effective learning experiences due to the unique characteristics of each classroom, considering varying student backgrounds and needs. Studies highlight the role of coursebooks, which are essential yet sometimes insufficient for addressing communicative and intercultural aspects of English language education. Hence, this qualitative study explores the adaptation of English language teaching materials by ten secondary school English teachers as part of the PRELIM3 Project. Specifically, it examines their perceptions of national coursebooks and their strategies for adapting project materials to enhance language teaching in the "PRELIM3" project, aimed at developing supportive language teaching materials aligned with the national curriculum for less developed regions in Türkiye. Data were collected through triangulation, including weekly teacher narrations of material adaptation experiences, semi-structured post-project training interviews, and analysis of weekly adapted coursebook activities. Additionally, teachers' conference presentations provided insights into classroom material adaptation, reflecting on students' language performance and reactions, besides teachers' use of materials. Content analysis and coding techniques were used to analyze narrations and interviews, while activities were evaluated based on English language skills targeted, alignment with lesson objectives, and responsiveness to student interests and needs. The study highlights the critical role of material adaptation in meeting students’ language learning needs, revealing teachers' perceptions and strategies in addressing the limitations of national coursebooks. Findings underscore the need for contextually responsive materials and offer insights to improve English language education in diverse classroom settings.